2013
DOI: 10.19173/irrodl.v14i4.1314
|View full text |Cite
|
Sign up to set email alerts
|

The extent of and reasons for non re-enrolment: A case of Korea National Open University

Abstract: <p>Despite continuous efforts to increase retention, dropout rates are high in distance universities. The objectives of this study were: 1) to investigate the extent and causes of non re-enrollment at a mega university, Korea National Open University; and 2) to suggest actions to improve the retention of students, in general, and those with higher risks of dropout in particular. A survey designed to establish the student demographics and the students’ main reasons for non re-enrollment was carried out du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
2
10
0
2
Order By: Relevance
“…These results strengthened prior studies on student persistence in the Open University contexts that student support services played a pivotal role in increasing student's persistence and performance (Choi, Lee, Jung, & Latchem, 2013;Dzakaria, 2005;Bharat Inder Fozdar et al, 2006;Ibrahim, Rwegasira, & Taher, 2007;Tait, 2004). In the same way, Barnett (2011) insisted the significance of the faculty's role in student persistence decision.…”
Section: Quality Of Registration Services 12 Participants Talked Abousupporting
confidence: 81%
See 1 more Smart Citation
“…These results strengthened prior studies on student persistence in the Open University contexts that student support services played a pivotal role in increasing student's persistence and performance (Choi, Lee, Jung, & Latchem, 2013;Dzakaria, 2005;Bharat Inder Fozdar et al, 2006;Ibrahim, Rwegasira, & Taher, 2007;Tait, 2004). In the same way, Barnett (2011) insisted the significance of the faculty's role in student persistence decision.…”
Section: Quality Of Registration Services 12 Participants Talked Abousupporting
confidence: 81%
“…In the Indonesia Open University, the students who are enrolled witihin four consecutive semesters are grouped into active students; otherwise those who do not enrol and do not register for any new course within four consecutive semesters will be classified into inactive students. A review of prior studies on student persistence in the Open University contexts revealed that student support has a pivotal contribution for increasing student persistence (Choi et al, 2013;Dzakaria, 2005;Fozdar et al, 2006;Ibrahim, Rwegasira, & Taher, 2007;Tait, 2004).…”
Section: Student Support In Open and Distance Learningmentioning
confidence: 99%
“…The populations in the study were college students at a four-year open university. This university was founded in 1972, which is the first lifelong educational institution in Korea and the first four-year national Open University in Korea [37]. It has one main campus that is located in Seoul and 13 local campuses.…”
Section: Context and Sample Characteristicsmentioning
confidence: 99%
“…Otras causas que destacan los investigadores: problemas tecnológicos (Frankola, 2001;Dupin-Bryant, 2004); las rigideces curriculares, la elección errónea de la carrera o acceder con expectativas equivocadas (Grebennikov y Shah, 2012); motivos económicos y sociales y la dificultad de los estudios (Duque, Duque y Surinach, 2013); la baja autoestima del estudiante (Roso-Bas, Pades y García, 2016); los bajos niveles de supervisión y apoyo docente (Montalvo, 2012); la escasa motivación, inadecuados diseños pedagógicos de las asignaturas y la baja cualificación de los docentes (Frankola, 2001); la escasa calidad de los programas con contenido relevante poco estructurados (Ivankova y Stick, 2007;Perry, Boman, Care, Edwards y Park, 2008); la falta de retroalimentación docente, la gran carga de trabajo y las dificultades para estudiar lejos del campus (Choi, Lee, Jung y Latchem, 2013). Por su parte, Fozdar, Kumar y Kannan (2006) ordenan las causas de abandono de esta manera: lejanía del centro de estudios, insuficiente apoyo académico, problema del tiempo de estudio, dificultad de asistir a los laboratorios, ausencia de interacción entre pares, dificultades para estudiar ciencias a distancia, dificultad del examen presencial, escasa capacidad de respuesta del centro de estudios.…”
Section: Los Resultados Las Causasunclassified